MENDORONG PERWUJUDAN DESA DIGITAL 4.0 MELALUI IDENTIFIKASI TAHAPAN PENGEMBANGAN DESA DIGITAL - Rike Anggun Artisa; Endah Mustika Ramdani; Rodlial Ramdhan Tackbir Abubakar (Politeknik STIA LAN Bandung, 2023)
The existence of technology as an acceleration in development emphasizes the importance of the need to adapt. This also has the implication that all levels of government up to the village level need to pay attention in order to optimize the development benefits that will be received by the community. West Java Province has a digital village program that aims to realize the welfare of rural communities through digitization, community capacity building, and maximizing village potential. However, not all villages know their current position well and what the stages of digital village development will be in the future. Therefore, a team of lecturers at the Politeknik STIA LAN Bandung in collaboration with Jabar Digital Service provided assistance to one of the villages in Bandung Regency in terms of identifying digital villages as well as the stages of their development in order to achieve digital village 4.0.